Comparison of Financial Performance Before and After Acquisition and Merger in Banking Sector Companies on The Indonesia Stock Exchange Period 2017-2021 - Hidayah, Nur; Budiyanti, Hety; Nurman; Sahabuddin, Romansyah; Ruma, Zainal (PT Maju Malaqbi Makkarana, 2024)
The Company's objective in carrying out mergers and acquisitions is to obtain better and more sustainable synergies, because mergers and acquisitions are believed to be able to achieve levels of economic scale, mastery of technology, guaranteed supply of raw materials, increased market reach, gain access to international companies and obtain additional funds. for company financing. The samples in this study were companies listed on the Indonesian Stock Exchange in 2017-2021 using a saturated sampling method to obtain 5 companies. The results of the research using descriptive analysis with paired sample t-test and Wilcoxon signed rank test showed that there were differences in the ratio of return on assets (ROA), operational costs to operating income (BOPO), loan to deposit ratio (LDR) and debt to assets ratio (DAR) between before and after M&A. Meanwhile, for return on equity (ROE), Non-Performing Loan (NPL), capital adequacy ratio (CAR), and Liquidity Coverage Ratio (LCR), there are no differences between before and after M&A. In the financial performance of banking subsector companies listed on the Stock Exchange Indonesia for the 2017-2021 period.